2017
DOI: 10.2298/sarh151117003j
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and contributing factors to overweight and obesity among the schoolchildren of Podgorica, Montenegro

Abstract: Introduction/Objective. Childhood obesity is an emerging public health problem. The national prevalence of child overweight/obesity in Montenegro has increased by one third in the last decade. As the overwhelming majority of Montenegrin population is urban, investigation of obesity and correlates among urban children is of special public health interest. The aim of this study was to investigate the prevalence of and contributing factors to obesity among schoolchildren of Podgorica. Method. The sample included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
4
11
1
Order By: Relevance
“…In the study Martinović et al (2015), WHO standards showed the highest rate of obese respondents and it is about 15.00% compared to 12.30% (CDC) and only 7.00% (IOTF) in boys and 6.50% (WHO), 5.60% (CDC) and 3.50% (IOTF) in girls. Approximately similar relationship of nutritional status was recorded in the research of Jakšić et al (2017), where e.g. the lowest percentage of normally fed subjects showed the WHO standard (61.60%) compared to 64.10% (CDC) and 67.80% (IOTF) in boys and 72.70% (WHO and CDC) and 74.10% IOTF) in girls.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the study Martinović et al (2015), WHO standards showed the highest rate of obese respondents and it is about 15.00% compared to 12.30% (CDC) and only 7.00% (IOTF) in boys and 6.50% (WHO), 5.60% (CDC) and 3.50% (IOTF) in girls. Approximately similar relationship of nutritional status was recorded in the research of Jakšić et al (2017), where e.g. the lowest percentage of normally fed subjects showed the WHO standard (61.60%) compared to 64.10% (CDC) and 67.80% (IOTF) in boys and 72.70% (WHO and CDC) and 74.10% IOTF) in girls.…”
Section: Discussionsupporting
confidence: 79%
“…A very similar relationship between the degree of nutrition of the respondents depending on the application of different standards was confirmed in the research of Milašinović et al, (2019) where WHO standards show the lowest percentage of malnourished and normally fed subjects, while the percentage of malnourished and obese according to WHO standards is significantly higher compared to CDC and IOTF. A review of the obtained results of all studies, it is concluded that malnutrition generally ranges from 0.90 to 6.20% for male respondents and in the range of 1.00-5.28% for female respondents (Baćović, 2020;Banjari et al, 2020;Banjević, 2019;Malović, 2019;Jakšić et al, 2017;Martinović et al, 2015). A slightly higher percentage of malnutrition was observed according to IOTF standards in the study of Milašinović et al, (2019), where malnutrition was 10.50% for boys and 7.50% for girls.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Increased nutrition on the side of boys compared to girls has been found in previous researches. Jakšić et al [18] stating the results: ,,Directorate for employment, labour and social affairs, data from 2014, the highest prevalence of OWOb (overweight/obesity) was recorded in Greece (44% of boys and 38% of girls) followed by Italy (36% vs. 34%), New Zealand (34% vs. 34%), USA (30% vs. 30%), while the lowest prevalence was recorded in Indonesia (11% vs.8%). Differences between prevalence of OWOb in favor of boys were found in China (24%vs.…”
Section: Discussionmentioning
confidence: 99%